Characteristics of TiO2/Solid electrolyte junction solar cells with I-/I-3(-) redox couple - Majid, Siti Rohana; Arof, Abdul Kariem; Buraidah, M.H.; Teo, L.P. (Elsevier, 2010)
Solid electrolytes comprising 55 wt.%chitosan-45 wt.%NH4I, 33 wt.%chitosan-27 wt.%NH4I-40 wt.%EC (ethylene carbonate) and 11 wt.%chitosan-9 wt.%NH4I-80 wt.%BMII (1-butyl-3-methylimidazolium iodide) have been prepared by the solution cast technique. The conductivity for the 55 wt.%chitosan-45 wt.%NH4I electrolyte is 3.73 x 10(-7) S cm(-1) at room temperature. Complexation between polymer and salt has been proven by Fourier transform infrared (FUR) spectroscopy where the carbonyl and amine bands in the spectrum of chitosan acetate shifted from 1645 and 1557 cm(-1)-1618 and 1508 cm(-1) in the polymer-salt spectrum. The addition of 40 wt.%EC to the 55 wt.%chitosan-45 wt.%NH4I electrolyte increased its conductivity to 7.34 x 10(-6)S cm(-1). The conductivity of the chitosan-NH4I electrolyte increased to 8.47 x 10(-4)S cm(-1) at room temperature on addition of 80 wt.%BMII. The plasticizer containing electrolyte is still a free standing film. The ionic liquid incorporated electrolyte is still solid, but with reduced mechanical stability due to the low polymer content. This shows that at such low content, chitosan is still able to host ionic conduction. A photovoltaic cell with configuration ITO/titanium dioxide (TiO2)-solid electrolyte with I/I-3 redox couple/ITO has been constructed using each electrolyte system. The short-circuit current density, J(sc) and open-circuit voltage, OCV obtained from the cell employing the polymer-salt electrolyte under white light illumination of intensity 56.4 mW cm(2) are 4.99 mu A cm(-2) and 0.15 V. respectively. The OCV for the cell with plasticizer containing electrolyte is 0.22 V and its J(sc) is 7.28 mu A cm(-2). The solar cell with ionic liquid incorporated in the solid electrolyte exhibited an OCV of 0.26 V and J(sc) of 19.23 mu A cm(-2), respectively. (C) 2009 Elsevier B.V. All rights reserved.